PENGARUH ECONOMIC VALUE ADDED DAN EARNING PER SHARE TERHADAP RETURN SAHAM (PENDEKATAN DATA PANEL) - Amyulianthy, Rafrini; K.Ritonga, Elsa (JURNAL FAIRNESS, 2015)
The purpose of this study is to examine the effect of Economic Value Added (EVA) and Earning per Share (EPS) on stocks return. This research was taken because there are still differences between the research study with each other. This research was conducted using secondary data. Population in this research was a with time company incorporated in the index LQ 45 in Indonesian Stock Exchange period 2013-2014. Sampling technique using was purposive sampling. There are 21 companies to analyzed. This study using multiple regression with panel data. Results shows that Economic Value Added (EVA) have positive significant effect on Stock Return, while Earning Per Share (EPS) also have positive significant on Stock Return. Adjusted R Square value was 0,395091 means 39,50% can explained by the independent variable, while 60,50% are influenced by the other variables which have not been included in the research model.